(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
In masterpieces of literature of different times and nations, in scientific works, in everyday life – practically in all spheres –we come across vivid, witty, memorable utterances. Some of them are frequently reproduced in speech by a definite number of speakers, others are just seldom quoted, but are not widely used. Such utterances usually express an interesting or unusual idea, convey a moral principle or a unique judgement. No doubt, that such utterances have their creators, but very often they lose their associative connection with the author; but there are also cases when the name of the author and the utterance are closely connected and go side by side. Such utterances are often called aphorisms. In everyday life the word “aphorism” is used to define any laconic and vivid utterance of a well-known author or an anonymous one (including those of folklore origin). The aphorism is a complex phenomenon of human creative activity that belongs both to language and speech. The article deals with the aphorism as a word and a notion and semantic peculiarities and thematic variety of aphorisms in W. Shakespeare’s sonnets. The semantics of the aphorisms singled out from W. Shakespeare’s sonnets are rich. Sometimes the aphorism taken from the sonnet conveys the main idea of the whole verse, sometimes contradicts it. Practically all of the sonnets deal with such topics as Love, Death, Time, Fame, Immortality, Good and Evil. The biggest thematic groups of the aphorisms analysed in the research are “Love” (32%) and “Human soul. Good and Evil in human soul” (28%). The most insignificant in quantity is the group “Power, wars and politics” (less than 2%). It is also necessary to mention that very often aphorisms as intertextual elements are transformed in this or that way. So, it was taken into consideration in the process of singling out the aphorisms out of the sonnets.